Application of the Quality Function Deployment (QFD) Method in Improving Service Quality Standards in Mie Gacoan Kediri - Ardian, Farid; Limantara, Arthur Daniel; Ningsih, Riris Eka Putri Wayudi; Fitriani, Rheina Indah (Universitas Nusantara PGRI Kediri, 2025)
Search objectives: This study intends to utilize the Quality Function Deployment (QFD) methodology to improve service quality standards in Mie Gacoan Kediri by synchronizing service improvement with customer expectations. Design/Method/Approach: Evaluation of the qualitative literature using the House of Quality (HoQ) model to identify and rank consumer needs. Service quality research is used to create systematic methods to turn consumer expectations into actionable improvements. Research Findings: The results of the study show that increasing wait times, service consistency, and responsiveness at Mie Gacoan Kediri can increase customer satisfaction. These fundamental attributes are ranked using QFD, resulting in actionable operational changes to meet customer expectations. Theoretical contribution/originality: This study shows that QFD can be used in high-demand fast-service situations, especially in the culinary industry, improving service quality management. The study uses a systematic qualitative approach, unlike previous quantitative studies, and provides in-depth insights into the components of services that are essential for consumer happiness in changing circumstances. Practitioner/Policy Implications: Mie Gacoan Kediri can use a research approach to recognize and implement service quality improvements driven by customer feedback. The results show that consumer loyalty in a competitive market requires concentrated personnel training, queue management, and service timeliness. Research limitations: This study uses secondary data from the literature; therefore, this study may not fully reflect the expectations of the Mie Gacoan Kediri client. Primary data obtained from surveys or interviews can support and improve the recommendations driven by QFD in subsequent research.